The role of IGRA in the diagnosis of tuberculosis infection, differentiating from active tuberculosis, and decision making for initiating treatment or preventive therapy of tuberculosis infection - Goletti, Delia; Delogu, Giovanni; Matteelli, Alberto; Migliori, Giovanni Battista (International journal of infectious diseases, 2022)
•Tuberculosis (TB) infection accounts for 2 billion people worldwide•TB infection is defined by immune response detection without clinical active disease•Tests for TB infection diagnosis lack accuracy to identify progressors to disease•Preventive therapy is a strategy to control TB spread worldwide•A TB infection registry is crucial for public health issues of TB control The World Health Organization estimated that a quarter of the global population is infected by Mycobacterium tuberculosis (Mtb). A better control of tuberculosis (TB) is based on the ability to detect Mtb infection, identifying the progressors to TB disease, undergoing to preventive therapy and implementing strategies to register the infections and treatment completion. we reviewed the literature regarding the tests available for TB infection diagnosis, the preventive therapies options and the cascade of care for controlling TB at a public health level. current tests for TB infection diagnosis as IFN-γ release assays or tuberculin skin tests are based on the detection of an immune response to Mtb in the absence of clinical disease. The main limit is their low accuracy to detect progressors to disease. New preventive treatments are available with short duration that are associated with better adherence. Options to register TB infections are presented. Tests to diagnose TB infection are available but they lack accuracy to identify the progressors from infection to TB disease. Shorter preventive TB therapy are available but need to be implemented worldwide. A TB infection registry is crucial for improving the cascade of care leading to a better TB control.